Basketball Game Between San Francisco 49ers and Edison High School Alumni - Watkins, Howard::::::::: (1987)
Art Wille holding his Lott #42 red and white jersey with Thomas Armstrong wearing green Boston Celtics 1984 World Champs T-shirt